Bilateral Orbital Cellulitis Causing Septic Pulmonary Embolism and Subsequent Bilateral Pneumothorax: A Rare Case Report - Osman FAO; Hirsi IM; Ali Jama SM; Ahmed AA; Yusuf AA; Dahir MO (International Medical Case Reports Journal)
Faisal Abdi Osoble Osman,1 Ibrahim Mohamed Hirsi,2 Shuayb Moallim Ali Jama,1 Abdirisak Abdikarin Ahmed,3 Abdisalam Abdullahi Yusuf,2 Mohamed Osman Dahir1 1Radiology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadish, Somalia; 2Pediatric Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadish, Somalia; 3Opthalmology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadish, SomaliaCorrespondence: Faisal Abdi Osoble Osman, Radiology Department, Mogadishu Somali Turkey, Recep Tayyip Erdogan Training and Research Hospital, Mogadishu, Somalia, Email Faisalosoble@gmail.comIntroduction: Septic pulmonary embolism is a serious and rare complication of orbital cellulitis. Orbital infection usually arises from adjacent soft tissue or hematogenous infections.Case: A 2-year-old girl presented with high-grade fever, cough, and bilateral eyelid swelling for 5 days preceded by edema and a perinasal facial skin furuncle. Examination revealed bilateral axial proptosis and orbital and thoracic CT bilateral orbital cellulitis, septic pulmonary embolism, and bilateral pneumothorax.Discussion: A rare but potentially fatal complication of periorbital cellulitis is septic embolism, which carries a high rate of morbidity and mortality. The infections that cause orbital cellulitis can be transmitted to the orbit through dehiscence of the bone wall or through venous drainage. This can lead to septicemia and subsequent serious complications, including septic pulmonary embolism, Cavernous sinus thrombosis, meningitis, and cerebral ischemia. Advanced and timely imaging is crucial to diagnose both orbital cellulitis and its thoracal complications.Conclusion: Early diagnosis of orbital cellulitis, timely investigations of its extracranial complications, and multidisciplinary involvement in patient management are crucial to prevent or treat complications such as septic pulmonary embolism and may improve patient prognosis.Keywords: Septic pulmonary embolism, SPE, Orbital cellulitis, OC and Pneumothorax, PTX